The Fund's Income Position For FY 2016 : Actual Outcome. (Policy Papers; Policy Paper, 2016)
This paper reports the Fund's income position for FY 2016 following the closing of the Fund's accounts for the financial year and completion of the external audit. FY 2016 net income, including income from surcharges, was unchanged from the amount of SDR 998 million projected in April. GRA net income for FY 2016 of about SDR 1 billion has been placed to the Fund's reserves, further strengthening the Fund's precautionary balances, which reached SDR 15.2 billion at the end of FY 2016. Following the completion of the Executive Board's review of the investment strategy for the Fixed-Income Subaccount and consistent with the discussions in April, currencies totaling about SDR 3.7 billion will be transferred to the Investment Account during September and October 2016. This comprises currencies equivalent to the net income retained in the GRA in FY 2014 (SDR 1.2 billion) and FY 2015 (SDR 1.5 billion), together with the currencies equivalent to the FY 2016 GRA net income of about SDR 1 billion.